Фольклорные маргиналии в белорусских медиа: cоздание и преодоление социальных мифов - Ratnikova, Irina (Acta Polono-Ruthenica, 2006)
Folk units as the special element of the modern cultural process are described in the article; the author takes into consideration the catch-words, anecdotes, parodies etc. Despite a lot of differences in the comparison with classical folklore, the „marginal” units become similar to it. In the most of cases it refers to: the mutual function in the process of socialization and in the cultural context, trade and political advertisement as the contemporary sphere of the folklore, expressed conviction about the possibility to order the world, to defense against the chaos. Furthermore, in the contemporary „folk communication” the scheme of universal deconstruction of social and cultural myths functions.It’s worth adding that in the function of universe, which organizes „classical” and contemporary verbal folk creativity, laugh, which creates much fairer, though an illusory „world of anticulture”, appears.